Surgical site infections in an abdominal surgical ward at Kosovo Teaching Hospital - Lul Raka,1,3 Avdyl Krasniqi,2,3 Faton Hoxha,2,3 Ruustem Musa,2 Gjyle Mulliqi,1,3 Selvete Krasniqi,1,3 Arsim Kurti,1,3 Antigona Dervishaj,1,3 Beqir Nuhiu,2 Baton Kelmendi,2 Dalip Limani,2,3 Ilir Tolaj.3 (The Journal of Infection in Developing Countries, 2007)
Background: Abdominal surgical site infections (SSI) cause substantial morbidity and mortality for patients undergoing operative procedures. We determined the incidence of and risk factors for SSI after abdominal surgery in the Department of Abdominal Surgery at the University Clinical Centre of Kosovo ƒv(UCCK).Methodology: Prospective surveillance of patients undergoing abdominal surgery was performed between December 2005 and June 2006. CDC definitions were followed to detect SSI and study forms were based on Europe Link for Infection Control through Surveillance (HELICS) protocol.Results: A total of 253 surgical interventions in 225 patients were evaluated. The median age of patients was 42 years and 55.1% of them were male. The overall incidence rate of SSI was 12%. Follow-up was achieved for 84.1% of the procedures. For patients with an SSI, the median duration of hospitalization was 9 days compared with 4 days for those without an SSI (p<0.001). Surgical procedures were classified as emergent in 53.3% of cases. Superficial incisional SSI was most common (55%). Clinical infections were culture positive in 40.7% of cases. Duration of operation, duration of preoperative stay, wound class, ASA score>2, use of antibiotic prophylaxis and NNIS class of >2 were all significant at p < .001. The SSI rates for the NNIS System risk classes 0, 1 and 2-3 were 4.2%, 46.7% and 100%, respectively.Conclusions: SSI caused considerable morbidity among surgical patients in UCCK. Appropriate active surveillance and infection control measures should be introduced during preoperative, intra-operative, and postoperative care to reduce infection rates.